Medidas higiénicas aplicadas en la preparación, manipulación y expendio de alimentos en los comedores del mercado municipal reina del cisne de la ciudad de Zamora, en el año 2014 - Reinoso Camacho, Rosa Mirella (2015)
This research, whose purpose was to determine compliance with the hygiene measures applied in the preparation, handling and sale of food vendors using Eaters Municipal Market Reina del Cisne in 2014, used the following methodology: descriptive, explanatory, qualitative, cross, bibliographic and fixed field. For its implementation it was made through the survey technique with his instrument the questionnaire consisting of closed questions applied to 37 vendors canteens and the observation guide in which the following parameters are assessed; situational characteristics, working as the application of sanitary measures, obtaining relevant data that 100% of the selling of local perform general cleaning and disinfection of the building 1 time per day, while the application of sanitary measures is obtained observed that the 100% of the population does not apply good hygiene measures when preparing and handling food and according to the test of knowledge was obtained that 68% of marketers have an average 27% knowledge and a high level of knowledge , on this subject, which allowed to obtain the analysis of the results, showing that people still have shortcomings in terms of hygiene measures which could jeopardize the health of the population. So an intervention plan based on training helping to improve the level of knowledge and management techniques in the preparation and handling and sale of food ran. Keywords: Hygiene measures, preparation, handling and sale of food, local food, Municipal Market